You in five acts - LaMarche, Una (Razorbill, an imprint of Penguin Random House, 2016)
At a prestigious New York City performing arts school, five friends connect over one dream of stardom. But for Joy, Diego, Liv, Ethan and Dave, that dream falters under the pressure of second-semester, Senior year. Ambitions shift and change, new emotions rush to the surface, and a sense of urgency pulses between them: Their time together is running out. Diego hopes to get out of the friend zone. Liv wants to escape, losing herself in fantasies of the new guy. Ethan conspires to turn his muse into his girlfriend. Dave pines for the drama queen. And if Joy doesn't open her eyes, she could lose the love that's been in front of her all along. An epic ensemble piece in the vein of Fame and Let's Get Lost , You in Five Acts is a eulogy for a friendship -- the heartbreaks, the betrayals, the inside jokes, the remember-whens. And the tragedy that changed everything.